Combination of Counter Pressure and Pelvic Rocking on Labor Pain Intensity Time I Active Phase: Kombinasi Counter Pressure dan Pelvic Rocking Terhadap Intensitas Nyeri Persalinan Kala I Fase Aktif - Nabila, Fania Elsa; Novyriana, Eka (Prosiding University Research Colloquium, 2023)
The number of labor pain that has been reported shows that the average in Indonesia is 85-90%. The Indonesian Hospital Association Data Center explained that 21% of the deliveries experienced were painful deliveries because they felt extreme pain. Factors that influence labor pain include physiological factors. The consequences that will occur in mothers who experience pain in labor are increased activity of the sympathetic nervous system which can result in changes in blood pressure, pulse, respiration, and skin color, nausea, vomiting, and also excessive sweating, while certain changes in behavior due to pain also often manifests as increased anxiety with constricted thinking, moaning, crying, hand movements and intense muscle tension throughout the body. The way that can be done to deal with labor pain is by applying counter pressure and pelvic rocking. To provide midwifery counter pressure and pelvic rocking care as a treatment for active phase I labor pain. This research is a type of case study. Participants in this study were 5 respondents who met the inclusion and exclusion criteria. Data obtained from observation and interviews. After 1 week of counter pressure and pelvic rocking, 5 participants experienced more optimal pain reduction. This is based on an assessment using a pain reduction instrument at the end of the application. The application of counter pressure and pelvic rocking has an effect on reducing labor pain in the active phase of the first stage.